Social capital strengthens agency among fish farmers: Small scale aquaculture in Bulacan, Philippines - Manlosa, Aisa O.; Albrecht, Julia; Riechers, Maraja (Frontiers in Aquaculture, 2023)
Using a case study approach focusing on Bulacan, Philippines, we examined three types of social capital (i.e. bonding, bridging, and linking) accessed by small scale aquaculture producers through fish farmers associations. The aim was to determine whether and how types of social capital contribute to promoting human agency among small scale aquaculture producers in the context of their livelihoods. Here, agency is considered an important part of sustainable livelihoods and is defined as people’s ability to choose in ways that align with their values and goals, and to act to realise their goals. Agency was analysed in relation to livelihood preconditions, processes, power, and possibilities. The premise of this paper is that types of social capital from fish farmers’ associations distinctly contribute to expanding and strengthening the agency of small scale aquaculture producers. The study found that all three types of social capital contributed to enhancing the resources that producers draw on for their livelihoods. The bonding and bridging types helped producers cope with various livelihood challenges by enabling access to mutual assistance and collective efforts for problem solving. The types of social capital were less effective in addressing issues of asymmetrical power relations which adversely affected livelihoods. All three types and particularly linking social capital contributed to expanding livelihood possibilities and enabling producers to explore new avenues for improving livelihoods, enhancing agency. The findings point to the distinct contributions and complementarity of different types of social capital to the exercise of agency in livelihoods. Attending to the different types of social capital and understanding how they are most beneficial in specific contexts as well as where they are insufficent, can improve priority-setting, targeting, and design for initiatives that seek to work with fish farmers organisations and other types of community-based organisations for livelihood improvements.